12 new susceptibility loci for prostate cancer identified by genome-wide association study in Japanese population - Ryo Takata (Nature Portfolio, 2019)
More than 170 genetic loci have been linked to prostate cancer risk, primarily based on genome-wide association studies (GWAS) in European population. Here, the authors performed a GWAS on a Japanese cohort of prostate cancer patients, finding 12 new susceptibility loci, and identifying a polygenic risk for Japanese prostate cancer.